Odpowiedzi

2010-03-25T17:54:34+01:00
A. (x³+6x²-2x+5)+(2x³-6x²+x-5)=
=x³+6x²-2x+5+ 2x³-6x²+x-5 =
= 3x³-x

b. (4a²-3ab+5b²)+(-a²-3ab-5b²)=
=4a²-3ab+5b²-a²-3ab-5b²=
=3a²-6ab

c.(5x⁴-2x²+6)+(-5x⁴+2x²-6)=
=5x⁴-2x²+6-5x⁴+2x²-6=
=0

d.(x³+2x²)-(x²+3x-4)=
=x³+2x²-x²-3x+4=
=x³+x²-3x+4

e. 2x³-(4x²-x)+(4x²-x-1)=
=2x³-4x²+x+4x²-x-1=
=2x³-1

f. 3a³b-(a-5a²b)+(a-8a³b)=
=3a³b-a+5a²b+a-8a³b=
= -5a³b+5a²b
2010-03-25T18:05:33+01:00
A. (x³+6x²-2x+5)+(2x³-6x²+x-5)=
=x³+6x²-2x+5+2x³-6x²+x-5=
=-x+3x³
b. (4a²-3ab+5b²)+(-a²-3ab-5b²)=
4a²-3ab+5b²-a²-3ab-5b²=
=-6ab+3a²
c.(5x⁴-2x²+6)+(-5x⁴+2x²-6)=
=5x⁴-2x²+6-5x⁴+2x²-6=
=0
d.(x³+2x²)-(x²+3x-4)=
=x³+2x²-x²-3x+4=
=x³+x²-3x+4
e. 2x³-(4x²-x)+(4x²-x-1)=
=2x³-4x²+4x+4x²-x-1=
=2x³+3x-1
f. 3a³b-(a-5a²b)+(a-8a³b)=
=3a³b-a+5a²b+a-8a³b=
=-5a³b+5a²b



życze naj...
;)